A novel approach to the implementation of Making Every Contact Count. (November 2022) - Hicken, Sandra; Needham, Jayne; Martin, Rose; Hall, Jo
Abstract: Background: Making Every Contact Count (MECC) is an approach to behaviour change introduced by Public Health England in 2008. Derbyshire have implemented MECC using the Quality Conversation (QC) programme which is based around health coaching and psychology skills and delivered remotely by qualified coaches. This study is an initial evaluation of the QC programme. Methods: Participants from Derbyshire health, social care, and voluntary organisations were invited to enrol on the QC programme. Before and after analysis of qualitative responses to example patient scenarios using an exact McNemar's test was done. A Wilcoxon signed-rank test was used to measure significant differences in quality conversation skills before and after the training programme. Participant data was analysed using SPSS software (version 28·0·0·0). Written consent for was provided by participants on completion of the feedback form. Findings: Between July 1, 2020, and March 31, 2022, there were 1277 participants on the core QC training. There were significant differences in knowledge and confidence in using QC skills following training (eg, confidence in active listening, Z = –189·09; p <0·0001). There was a significant difference in the proportion of QC-consistent responses (eg, skills such as validation and open questions, p<0·0001). Further, there was a significant difference in self-rated confidence with responding to example patient scenarios pre and post-training (Z = –118·81; p <0·0001). At 2-month follow-up, 91% of follow-up respondents (N =225) strongly agreed or agreed that the learning from the QC programme had been relevant to their role. Interpretation: QC is a novel approach to the implementation of MECC, through reframing the focus to supporting changes in staff communication behaviours. Findings presented suggests QC might represent a scalable approach to the effective implementation of MECC. This is an important finding given the potential of MECC to support health and social care systems to address health inequalities and support the personalisation agenda. Funding: Joined Up Care Derbyshire Integrated Care System.